Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-072
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Secondary Flow in a Turbine Cascade by 3D Airfoil Design and Endwall Contouring

Abstract: A highly loaded turbine cascade has been redesigned with the objective to reduce the secondary flow by applying endwall contouring and 3D airfoil design in the endwall regions. The overall loading and the axial area ratio of the cascade have been kept constant. With the tools of a 3D design environment a systematic study has been carried out regarding several features of the endwall pressure distribution and their influence on the secondary flow. Two optimized configurations have been investigated in a high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…The considerable extent of laminar flow on low pressure turbine blades therefore necessitates the use of realistic transition modeling if reasonable predictions of profile loss, and hence efficiency, are sought. Figure 4 shows that the structure of the secondary flow at 125%C X is the same as that reported in other studies of low pressure turbine blades in linear cascade [2,3,10,11]. Furthermore, Figure 3 and Figure 4 show that there is considerable variation in stagnation pressure loss and exit yaw angle in the secondary flow region (from approximately 0% to 20% span).…”
Section: Figure 3: Pitchwise Mass Averaged A) Stagnation Pressure Lossupporting
confidence: 78%
See 2 more Smart Citations
“…The considerable extent of laminar flow on low pressure turbine blades therefore necessitates the use of realistic transition modeling if reasonable predictions of profile loss, and hence efficiency, are sought. Figure 4 shows that the structure of the secondary flow at 125%C X is the same as that reported in other studies of low pressure turbine blades in linear cascade [2,3,10,11]. Furthermore, Figure 3 and Figure 4 show that there is considerable variation in stagnation pressure loss and exit yaw angle in the secondary flow region (from approximately 0% to 20% span).…”
Section: Figure 3: Pitchwise Mass Averaged A) Stagnation Pressure Lossupporting
confidence: 78%
“…Specifying transition at the leading edge on the suction surface resulted in profile losses of approximately 0.04. Other studies of turbine profiles that compared numerical predictions with experiments showed similar behavior [10,11]. Specifying transition at the leading edge on the suction surface is clearly physically unrealistic as the acceleration from the leading edge to peak suction on low pressure turbine blades should keep the boundary layer laminar [12].…”
Section: Figure 3: Pitchwise Mass Averaged A) Stagnation Pressure Losmentioning
confidence: 90%
See 1 more Smart Citation
“…Duden et al [8] applied axisymmetric profiling to an endwall and found that the extent of the secondary flow was reduced as well as the secondary-flow losses. In two companion works, Harvey et al [11] and Hartland et al [12] have presented the design and experimental validation of a passage subject to nonaxisymmetric endwall profiling.…”
Section: Introductionmentioning
confidence: 98%
“…Strategies to overcome the aerodynamic losses arising from secondary flows have included the use of endwall profiling and/or secondary air injection to alter the underlying vortical flow within a passage e.g., see [8][9][10][11][12]. Duden et al [8] applied axisymmetric profiling to an endwall and found that the extent of the secondary flow was reduced as well as the secondary-flow losses.…”
Section: Introductionmentioning
confidence: 98%